Pemeliharaan Gardu Distribusi UTCA Tipe Cantol yang dilakukan Oleh PT. PLN Persero ULP Anyer - Damayanti, Jahra; Fatkhurrokhman, Mohammad (Fakultas Teknik UMRI, 2025)
Distribution substation maintenance is an important measure to ensure the continuity of a reliable and safe electricity supply for consumers. This study focuses on the maintenance of cantilever-type distribution substations carried out by PT. PLN (Persero) ULP Anyer in Serang, Banten. This maintenance aims to prevent sudden equipment failures, ensure safety, and enhance the efficiency and durability of the electrical distribution system. The research method employed is qualitative descriptive, involving observation, interviews, and literature review conducted over one month, from July 1 to 31, 2024. The results of the study indicate that the cantilever-type distribution substation at PT. PLN (Persero) ULP Anyer is in good condition, with key components such as transformers, PHB-TR panels, and protective equipment well-maintained and functioning optimally. However, several areas requiring attention were identified, such as the installation of hazard signs and substation numbers to enhance safety and substation identification. Overall, the routine maintenance carried out has proven effective in maintaining the stability and reliability of the electricity distribution system.